1989
DOI: 10.1104/pp.91.4.1372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of C4 Photosynthesis

Abstract: A theoretical model of the composition of the inorganic carbon pool generated in C4 leaves during steady-state photosynthesis was derived. This model gives the concentrations of CO2 and 02 in the bundle sheath cells for any given net photosynthesis rate and inorganic carbon pool size. The model predicts a bundle sheath CO2 concentration of 70 micromolar during steady state photosynthesis in a typical C4 plant, and that about 13% of the inorganic carbon generated in bundle sheath cells would leak back to the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Results of recent experiments support the view of Jenkins et al (1989). Ludwig et al (1998) transformed the NADP-ME-type C4 dicot Flaveria bidentis with a construct encoding the tobacco chloroplast CA lacking a transit sequence.…”
Section: Plantsmentioning
confidence: 61%
See 1 more Smart Citation
“…Results of recent experiments support the view of Jenkins et al (1989). Ludwig et al (1998) transformed the NADP-ME-type C4 dicot Flaveria bidentis with a construct encoding the tobacco chloroplast CA lacking a transit sequence.…”
Section: Plantsmentioning
confidence: 61%
“…Furthermore, it was postulated that CA must be excluded from the bundle sheath cells to avoid loss of accumulated CO 2 due to its conversion to HCO 3 -and leakage of the latter back to mesophyll cells through plasmodesmata (Burnell & Hatch 1988). However, results of later modelling studies indicated that effects of CA in the bundle sheath would be less severe (Jenkins, Furbank & Hatch 1989).…”
Section: Plantsmentioning
confidence: 99%
“…Rubisco and the other enzymes of the photosynthetic carbon reduction cycle, located in the bundle sheath cell chloroplasts, reduce the released CO 2 and the remaining three-carbon compound diffuses back into the mesophyll cells, where it can undergo another round of the C 4 acid cycle. This combination of anatomical and biochemical characteristics, including the cell-specific expression of enzymes, results in an efficient CO 2 concentrating mechanism whereby the CO 2 level in the C 4 bundle sheath cells is up to 20 times that of the surrounding mesophyll cells and photorespiration is essentially eliminated (Jenkins et al, 1989).…”
mentioning
confidence: 99%
“…After measuring the rate of 180 loss due to the nonenzymic reaction, the enzyme-catalyzed rate was determined by adding a sample of extract containing CA. CA activity in the CO2 hybridration direction was deduced from the increase in rate of 180 loss over that observed without enzyme by applying this factor to the nonenzymic first order rate constant for the CO2 hydration reaction (25°C and an ionic strength of 0.1 [7] …”
mentioning
confidence: 99%